“Pero le juro que no soy el padre”: apuntes sobre los criterios de la Corte Suprema en los procesos de impugnación de reconocimiento de filiación extramatrimonial - Santome Sánchez, Aldo (2024)
The recognition of extramarital filiation is one of the greatest challenges for family law today.In this line, the present article follows a review and jurisprudential analysis of the criteria that the Supreme Court has developed and adoptedfor the proceedings challenging the recognition of extramarital filiation. In order to do so, the author reviews the concepts of kinship, filiation, family legal relationship and the best interest of the child.